Daniel in the lion's den (Manila : WS Pacific Publications, 2019)
"Daniel is a friend of the king. But not everyone likes that. Some people are jealous of Daniel. They make sure that re receives a terrible punishment. Daniel is thrown into a den with lions! Find out what happens next in this special bible story."--Cover.
On board pages.
Keywords: Bible stories